2010
DOI: 10.1007/s12665-010-0458-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the potential for bank filtration in a water-stressed megacity (Delhi, India)

Abstract: In the densely populated semi-arid territory around Delhi, the water demand is rising continuously, while the surface-and groundwater resources are threatened by contamination and overexploitation. This is a typical scenario in many newly industrialising and developing countries, where new approaches for a responsible resources management have to be found. Bank filtration holds a great potential, thus being a low tech method and benefiting from the storage and contaminant attenuation capacity of the natural so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 42 publications
2
32
0
1
Order By: Relevance
“…Thus, continuing investigations should apply higher temperature differences, even at the risk of inducing the collapse of the system. Other studies on bank filtration in tropical and sub-tropical countries showed that purification during infiltration still works at higher temperatures of up to 35°C [37,38]. Additionally, more replicates are recommended to reduce the variability/patchiness between the enclosures and the development of unknown artefacts.…”
Section: Microbial Activitymentioning
confidence: 99%
“…Thus, continuing investigations should apply higher temperature differences, even at the risk of inducing the collapse of the system. Other studies on bank filtration in tropical and sub-tropical countries showed that purification during infiltration still works at higher temperatures of up to 35°C [37,38]. Additionally, more replicates are recommended to reduce the variability/patchiness between the enclosures and the development of unknown artefacts.…”
Section: Microbial Activitymentioning
confidence: 99%
“…The systems are often not operating to their full capacity and treatment is hampered due to various reasons, such as lack of trained staff and inadequate supply of spare parts. There is a growing interest in adopting new technologies for water recycling within cities among which are bank filtration (Lorenzen et al 2010), reed beds, natural wetlands, constructed wetlands (Mittal et al 2006) and soil aquifer treatment systems (Kumar 2009). Successful natural treatment systems are exemplified by the ECW, which have been in existence for hundreds of years, natural treatment ponds with aquatic plants in Pune, and numerous constructed wetlands in other cities of India (CPCB 2002).…”
Section: Pollution Abatement Activities Of the Governmentmentioning
confidence: 99%
“…Since there is no alternative source of water, users have adapted themselves to the situation (by changing the crops) and have continued to use the water available, irrespective of its quality. Low-cost technologies like riverbank filtration are also being tested for their relative merits (Lorenzen et al 2010), and their wider use can be expected in the future. In general, community reflections on the past and present uses of wastewater, and the related advantages and disadvantages were similar to those stated by wastewater farmers of many other countries, but the responses were mixed for the same location, reflecting the individual experiences (Table 8).…”
Section: Wastewater Use Livelihoods and Financial Benefitsmentioning
confidence: 99%
“…For instance, some have focused on internal interactions (Bidhendi et al 2008, Lorenzen et al 2010, Bai et al 2012, distant interactions (Sohel et al 2003, Abraham 2010, Deines et al 2016, socioeconomic interactions Shi 2003, Bidhendi et al 2008), or environmental interactions (Tortajada and Castelan 2003, Lorenzen et al 2010, Bai et al 2012, Yan et al 2012. This is partially due to insufficient integrated conceptual frameworks that systematically analyze various components simultaneously.…”
Section: Introductionmentioning
confidence: 99%